UTILIZATION OF YOGURT AS A NATURAL ANTIMICROBIAL AGENT TO INHIBIT THE GROWTH OF PATHOGENS IN AVOCADO JUICE - Akhmad Mustofa; Nanik Suhartatik; Angraini Mariam Saraswati; Beti Cahyaning Astuti; Eko Yuliastuti (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Avocado juice consider as perishable food and easily contaminated to pathogenic bacteria. Previous research showed that avocado juice sold in Surakarta city was contaminated with coliform, Salmonella-Shigella sp, and also high in aerobic plate count. Yoghurt was fermented milk which contain lactic acid and have an antimicrobial activity. The aims of the research was to determine the ability of yoghurt to inhibit the growth of contaminant in avocado juice. Completely randomized design with 2 factors were applied. The factor was yoghurt concentration and the second factor was incubation time. The results showed that the lowest number of TPC microbes was found in avocado juice with the addition of 10% yogurt, namely 6.16 ± 0.19 log CFU/ml, the lowest amount of Yeast/Mold was found in avocado juice with the addition of 10% yogurt, namely 4.97 ± 0, 35 log CFU/ml, the lowest amount of coliform was found in avocado juice with 15% of yogurt (2.83 ± 0.00 log CFU/ml), the lowest amount of total Salmonella-Shigella was found in avocado juice with the addition of 20% yoghurt (2.70 ± 0.17 log CFU/ml) and the lowest amount of Total Staphylococci was found in avocado juice with the addition of 15% yogurt (4.00 ± 0.00 log CFU / ml). Yoghurt were not able to inhibit the growth of contaminant in avocado juice. Another natural antimicrobial agent should be explored to maintain food safety, especially for minimally processed food. Keyword: Avocado Fruit Juice, Microbiological Contamination, Yogurt